CONTRA RADICALISM THROUGH THE INTERPRETING VERSE OF JIHAD (CASE STUDY ON NU ONLINE PLATFORM) - Rahmawati, Kholifah; Heriyanto, Heriyanto (Journal of Terrorism Studies, 2023)
This research attempts to map counter-radicalism in religious-based efforts carried out by a religious organization through digital platforms. With a virtual ethnographic model that focuses on text analysis, it is known that NU Online has carried out counter-radicalism through a religious interpretation approach. By targeting jihad verses, counter-radicalism is done in three ways, namely, deconstruction of the meaning of jihad, reconstruction of the meaning of jihad, and counter-narrative of jihad verses with peace verses. Apart from that, NU Online is also increasing its influence in the digital space by strengthening its narrative and identity as a moderate group with national commitment and an Indonesian perspective.